2013
DOI: 10.1007/s00217-013-1982-1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of solvent type in estimating antioxidant properties of phenolic compounds by ABTS assay

Abstract: ABTS assay belongs to the most popular methods employed for estimating antioxidant activity. However, researchers seldom pay attention to specific factors influencing the determination of antioxidant activity of the examined compounds and mixtures. The paper shows that the type of alcohol used significantly influences the estimation of antioxidant activity of phenolic compounds in ABTS assay, namely that their antioxidant activity increase with the lengthening of the aliphatic chain in alcohol. It results rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 28 publications
3
24
0
3
Order By: Relevance
“…The usually applied characteristic maxima to monitor are 414-417 nm and 730-734 nm ( Table 2); however, the latter is the recommended range due to the possible interference of many samples, which can be expected at lower wavelengths, resulting in the underestimated antioxidant capacity [37]. It is important to consider that ABTS •+ absorbance maximum bands shift a little in different solvents due to the solvatochromic effect: methanol (744-745 nm), ethanol (753 nm), and propanol-1 (757 nm) [38,39]. The pH impacts the λ max either, for example, in 0.1 M acetate buffer pH 5 a hypsochromic shift is observed with a maximum at 728 nm [40].…”
Section: Abts/pp Basic Chemistrymentioning
confidence: 99%
“…The usually applied characteristic maxima to monitor are 414-417 nm and 730-734 nm ( Table 2); however, the latter is the recommended range due to the possible interference of many samples, which can be expected at lower wavelengths, resulting in the underestimated antioxidant capacity [37]. It is important to consider that ABTS •+ absorbance maximum bands shift a little in different solvents due to the solvatochromic effect: methanol (744-745 nm), ethanol (753 nm), and propanol-1 (757 nm) [38,39]. The pH impacts the λ max either, for example, in 0.1 M acetate buffer pH 5 a hypsochromic shift is observed with a maximum at 728 nm [40].…”
Section: Abts/pp Basic Chemistrymentioning
confidence: 99%
“…Apart from their structural characteristics (number and position of -OH groups, inductive effects of other substituents present in the antioxidant molecule, steric hindrance/accessibility, packaging of an antioxidant around reactive species) the reactivity of an antioxidant depends significantly on reaction conditions such as solvent polarity, pH, temperature, type and concentration of reactive species. 3,[6][7][8][9][10][11][12][13][14] Since the selection of the method, the time and reaction conditions adopted to evaluate the content of antioxidants in a given sample significantly impact the determined values and, due to the fact that these parameters in a number of articles are relatively poorly described, it is very difficult to compare the results of AOP obtained for similar samples in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the solubility of these stable radicals in water and in different alcohols but also to the ability of various antioxidants to transfer electrons in different media. 34 The results concerning the high positive linear correlation between TPC and antioxidant capacity support a strong contribution of phenolic compounds to the antioxidant properties of the breadfruit extracts. Although Englberger et al 35 have observed that breadfruits contain carotenoids and other lipophilic compounds with antioxidant activity that could interfere with the observations made in this study, the use of water extracts made it possible to identify many phenolics and other compounds of similar solubility, as apparent in the characterization of bioactive compounds by LC-MS.…”
Section: Discussionmentioning
confidence: 79%
“…It is our experience that ABTS assays tend to show better results when water‐soluble antioxidants are tested, whereas DPPH assays better detect alcohol‐soluble components. This may be related to the solubility of these stable radicals in water and in different alcohols but also to the ability of various antioxidants to transfer electrons in different media …”
Section: Discussionmentioning
confidence: 99%